Heat loss or heat uptake? Skin temperature in Antillean manatees (Trichechus manatus manatus, Sirenia: Trichechidae) in Belize - Erdsack, Nicola; Galves, Jamal A.; Powell, James E. (Revista de Biología Tropical, 2023)
Introduction: The two subspecies of the West Indian manatee (Trichechus manatus), Florida manatees (T. m. latirostris) and Antillean manatees (T. m. manatus), face different environmental challenges. While Florida manatees have to cope with winter water temperatures below their lower critical temperature of ~ 20 °C and air temperatures below freezing, Antillean manatees live in year-round warm Caribbean waters. Sirenians lack effective thermal insulation and have limited capability of controlling peripheral heat loss. Although severe cold related health issues and mortality are primarily known in Florida manatees, it can be assumed that Antillean manatees and other extant sirenians share the cold-sensitivity, but hardly ever experience it. Contrarily, during summer, Antillean manatees may face the opposite form of thermal stress by being exposed to water temperatures close to their body temperature. However, the upper critical temperature of manatees is not known. Objective: To improve understanding of the impact of high ambient temperatures on manatee physiology. Methods: We measured skin temperature in six Antillean manatees in two different habitats in Belize, and compared the results to skin temperatures measured in two captive Florida manatees. Results: We found a similar temperature distribution pattern over the body surface in both subspecies, but significantly higher temperatures and larger temperature ranges among measuring points in Antillean manatees as compared to Florida manatees. In one Antillean manatee, skin temperature was consistently lower than ambient water temperature by up to 2.5 °C. This implies potential heat uptake from the environment, in contrast to the heat loss experienced by Florida manatees at low water temperatures, apparent in skin temperatures above ambient water temperature. Conclusions: Our findings suggest that heat stress may be a more likely risk for manatees in warm tropical waters. Despite the small sample size, our results present important findings towards understanding thermal tolerance and impact of high ambient temperatures on manatee physiology.